Pemetaan Genangan Setelah Hujan Secara Partisipatif di Universitas Islam Negeri Sultan Syarif Kasim Riau - Cindy Aulia; Dahnila Aini; Nurul Hikmah; T. Rivaldo Putra; Fatmawati Fatmawati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Puddles after rainfall remain a common environmental issue in urban areas, including in higher education environments. At Sultan Syarif Kasim State Islamic University (UIN Suska) Riau, post-rain flooding often disrupts academic activities and reduces comfort among campus residents. This study aims to identify the locations of post-rain flooding, analyze the contributing factors, and explore the perspectives and proposed solutions of the campus community through a participatory mapping approach. The study employed a qualitative descriptive method supported by Geographic Information System (GIS) spatial analysis. Data were collected through field observations, interviews with students, lecturers, and staff, and GPS-based flood point mapping. Results show that puddles frequently occur in main parking areas, inter-faculty roads, and flat areas around the Student Activity Center. The main causes include inadequate drainage systems, clogged channels due to waste, limited infiltration zones, and impervious surfaces. The campus community suggested solutions such as improving drainage, constructing infiltration wells, and adopting the green campus concept. Participatory mapping proved effective not only for identifying environmental problems but also for raising ecological awareness and shared responsibility among the academic community.